Pengembangan Media Interaktif Berbasis HTML5 Digital Story Pocketbook Muatan Pembelajaran Bahasa Indonesia Kelas IV - Agil Aryanto; Sukardi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The development of technology has entered the field of education, with the most noticeable being the significant growth of digital-based learning media. This research discusses the development of interactive learning media called Digital Story Pocketbook for Indonesian Language Class IV, Phase B, focusing on the topic of Discovering Intrinsic Elements of Narrative Texts. The research utilizes the Research and Development (R&D) method, aiming to produce and test the effectiveness of a product, following the Borg and Gall model consisting of 8 stages tailored to the research needs, including: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) initial testing (small-scale); (7) product revision; (8) field testing (large-scale). The results of developing the Digital Story Pocketbook for Indonesian Language Class IV, Phase B, on the topic of Discovering Intrinsic Elements of Narrative Texts, indicate that the product is deemed suitable based on the media expert's validation score of 93.3% and content expert's validation score of 90%. The practicality of the Digital Story Pocketbook is evident from the response of the learners, with a score of 90.5%, and the N-gain presentation of 77.2% demonstrates the effectiveness of the Digital Story Pocketbook as a learning media.